2021
DOI: 10.3390/ijerph18052757
|View full text |Cite
|
Sign up to set email alerts
|

Time for ‘Green’ during COVID-19? Inequities in Green and Blue Space Access, Visitation and Felt Benefits

Abstract: We hypothesized that visits to green and blue spaces may have enabled respite, connection and exercise during the COVID-19 pandemic, but such benefits might have been inequitably distributed due to differences in financial difficulties, opportunities to work from home, and localized restrictions in spatial mobility generated by ‘lockdowns’. A nationally representative online and telephone survey conducted in 12–26 October on the Social Research Centre’s Life in AustraliaTM panel (aged ≥ 18 y, 78.8% response, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 37 publications
7
64
2
Order By: Relevance
“…This is because a large area of green space noticeably reduces sources of stress, such as noise levels [ 56 , 57 ], air dust pollution [ 41 , 58 , 59 , 60 , 61 ] and gases, including carbon dioxide [ 62 , 63 ], which in turn leads to an improvement in air quality conditions in that area. The COVID-19 pandemic has highlighted the importance of green-blue spaces as areas that can also mitigate the negative effects of social isolation on mental health [ 64 , 65 , 66 , 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is because a large area of green space noticeably reduces sources of stress, such as noise levels [ 56 , 57 ], air dust pollution [ 41 , 58 , 59 , 60 , 61 ] and gases, including carbon dioxide [ 62 , 63 ], which in turn leads to an improvement in air quality conditions in that area. The COVID-19 pandemic has highlighted the importance of green-blue spaces as areas that can also mitigate the negative effects of social isolation on mental health [ 64 , 65 , 66 , 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rogers et al (2020) found that people without garden access engaged in less vigorous physical activities than people with gardens during lockdown. Other studies indicated that the level of physical activity increased with more visits to public green spaces (Ugolini et al, 2021;Astell-Burt and Feng 2021). Interestingly, Lesser and Nienhuis (2020) found people who usually were active (> 150 min of physical exercise per week) spent more minutes per week engaging in outdoor physical activity in nature than less active respondents.…”
Section: Physical Activity and General Physical Healthmentioning
confidence: 96%
“…Several of these same studies also tested for differences in nature exposure and associations with health by gender/sex, finding no differences in most analyses. The Australian survey mentioned above found that men spent less time in natural areas during lockdown but they also reported that these areas provided more solace, respite, and feelings of social connection than women (Astell-Burt & Feng, 2021). The April 2020 U.K. survey found the opposite, however; women reported that green space benefited their health more during the lockdown than before the lockdown relative to men (Burnett et al, 2021).…”
Section: Variations In Nature Contact Changes and Nature-health Associations By Sociodemographic Economic And Racial/ethnic Groupsmentioning
confidence: 97%
See 2 more Smart Citations